G154 Paediatric exercise tolerance test in District General Hospitals in England and Wales – A survey of current practice and single centre experience over 10 years. (27th April 2016) - Popat, A; Wong, MCM; Singh, B; Rahman, MM
Abstract : Aims: Paediatric Exercise tolerance test (ETT) is a well-established component in the investigation of cardiac disease in children. We aimed to investigate the current practice of ETTs amongst Paediatricians across England and Wales, and provide practice and safety data from our local experience. Methods: An online survey on the current practice of ETTs was distributed and completed by 49 members of the Paediatricians with Expertise with Cardiology Special Interest Group (PECSIG) between November 2014 and March 2015 and results analysed. Simultaneously a retrospective review of all patients <16 years undergoing ETTs at our local DGH from Dec 2003 to Dec 2013 was carried out. Data was collected on demographics, indication, supervision, result, adverse events, outcome, and whether pre-test ECGs and echocardiograms were performed. Adverse events were defined as those requiring cardiopulmonary resuscitation, cardioversion, defibrillation, or acute anti-arrhythmic therapy. Results: Paediatric ETTs are carried out in 23/49 (47%) of responding units. In 20/21(95%) units, the decision to do the test locally was made by a consultant, with some units having age and clinical risk criteria. 18/21 (85%) of units have Paediatric doctors supervising at least some of the tests. Of the units which did not carry out any ETTs locally, unavailability of trained professional (14/20, 70%), followed by concerns regarding safety (11/20, 55%) were the most commonly cited barriers. Over 10 years, our local data identified 53 tests carried out on patients aged 7–15 years (mean 12.6 years). 7(13%) had Congenital Heart Disease and 7(13%) had abnormal baseline ECGs. 3(5.7%) were positive for exercise related arrhythmia. An adverse event occurred in 1/53 (1.9%). Following testing, 23 (43%) patients were discharged. Conclusion: ETT practice vary across DGHs in England and Wales, with availability of trained staff and safety being the main barriers to its local provision. Our local rate of adverse event was 1.9% over 10 years. Clinically significant arrhythmias were found in 5.7%. Our data support the notion that Paediatric ETTs can be safely performed in a DGH and may reduce referrals to tertiary centres. Further studies will be beneficial in formulating evidence based recommendations for Paediatric ETTs in the UK.